Therapy-induced senescent cancer cells contribute to cancer progression by promoting ribophorin 1-dependent PD-L1 upregulation - Hyun Jung Hwang; Donghee Kang; Jisoo Shin; Jonghun Jung; Soyeon Ko; Kyung Hee Jung; Soon-Sun Hong; Ji Eun Park; Myung Jin Oh; Hyun Joo An; Wen-Hao Yang; Young-Gyu Ko; et al. (Nature Communications)
Abstract Conventional chemotherapy- and radiotherapy-induced cancer senescence, which is characterized by poor proliferation, drug resistance, and senescence-associated secretory phenotype, has gained attention as contributing to cancer relapse and the development of an immunosuppressive tumor microenvironment. However, the association between cancer senescence and anti-tumor immunity is not fully understood. Here, we demonstrate that senescent cancer cells increase the level of PD-L1 by promoting its transcription and glycosylation. We identify ribophorin 1 as a key regulator of PD-L1 glycosylation during cancer senescence. Ribophorin 1 depletion reduces this elevated level of PD-L1 through the ER-lysosome-associated degradation pathway, thereby increasing the susceptibility of senescent cancer cells to T-cell-mediated killing. Consistently, ribophorin 1 depletion suppresses tumor growth by decreasing PD-L1 levels and boosting cytotoxic T lymphocyte activity in male mice. Moreover, ribophorin 1-targeted or anti-PD-1 therapy reduces the number of senescent cancer cells in irradiated tumors and suppresses cancer recurrence through the activation of cytotoxic T lymphocytes. These results provide crucial insights into how senescent cancer cells can escape T-cell immunity following cancer treatment and thereby contribute to cancer recurrence. Our findings also highlight the therapeutic promise of targeting senescent cancer cells for cancer treatment.